A Study on College English Effective Teaching and Learning - Guoliang, Zhang (Pacific International Journal, 2023)
College English plays a crucial role in the comprehensive development of Chinese university students. Effective teaching practices are essential in college English education, directly influencing students' language acquisition and proficiency. This paper examines research on effective teaching strategies in college English, focusing on instructional strategies, teacher-student interaction, and assessment methods. Communicative approaches, technology integration, supportive environments, differentiated instruction, formative assessment, and constructive feedback contribute to enhancing students' language learning outcomes. However, challenges such as weak listening and speaking skills and the need to redefine teaching effectiveness exist. The paper highlights the importance of incorporating humanistic elements in college English teaching and addresses current issues in teaching and learning. Emphasizing the role of teachers, evidence-based strategies are proposed to create engaging and dynamic learning environments that foster language development.